Ski & Snowboard Australia Alpine athlete pathway (Ski & Snowboard Australia, 2019)
Alpine Skiing and Snowboard Cross are the first athlete pathways to be developed using Sport Australia`s FTEM framework which divides `the whole of sport pathway continuum` into four phases - Foundation, Talent, Elite and Mastery. FTEM recognises that each stage of sport development is unique and is an important stepping stone for athletes with a goal to succeed in high performance sport.